SPIN DRY-PAD: MESIN PUTAR PENGERING PADI BERBASIS SISTEM OTOMASI UNTUK MENINGKATKAN KUALITAS DAN PRODUKTIVITAS PADI UD SUMBER REJEKI - Adhim, Mochammad Machrus; Wahyudi, Mochammad; Yunansha, Dony; Maulida, Nadhifa; Ayu, Nur Ika Puji (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
The climate change causing rice production decreases, particularly on rice drying process before being milled rice. At the observation at UD Sumber Rejeki that the drying process of rice in the rainy season suffered a loss of 900,000/ton. To minimize the production process failed in drying rice process, made a rice dryer technology with automatic dialing systems, as well as controlling the temperature and moist content in the precision can be set as needed (Spin Dry-Pad). The Result when using Spin Dry Pad, UD Sumber Rejeki can increase domestic rice production during rainy season with operational cost only 191.500/ton and the quality of rice produced according to the standart PUSLITBANG agriculture department of Indonesia, which the moisture of rice is 14%.